Nanocrystalline Cellulose as Effect Pigment in Clear Coatings for Wood. (27th August 2013) - Vlad-Cristea, Mirela Simona; Landry, Véronic; Blanchet, Pierre; Ouellet-Plamondon, Claudiane
Abstract : Nanocrystalline cellulose (CNC) is a renewable material with high potential in many applications. Due to its unique self-assembly and optical properties, CNC tends to behave as an iridescent pigment. The aim of this research was to explore the potential of CNC as an effect pigment in wood coatings. CNC-based coatings were developed from an aqueous CNC solution, a UV-curable water-based clear coating formulation, several colorants, and specialized additives. In this paper, the morphology of the resulting CNC films was investigated through circular dichroism and optical microscopy under polarized light. The effect of the CNC surface charge changes was monitored through zeta potential measurements. Color changes, or travel, and flop index were used to assess the iridescent effect of the coatings containing CNC. The experimental wood coatings contained CNC showed that the enhancement of the iridescent effect depends on the distribution and alignment of the CNC rod-like particles in order to generate the right pitch in the helical structure and their interaction with the polymer matrix as well with the additives. In conclusion, CNC could be successfully used as effect pigment in finishing systems, which can enhance the attractiveness and bring out the special grain of various types of wood.